156k views
1 vote
Use the substitution x = 2 − cos θ to evaluate the integral ∫ 2 3/2 ( x − 1 3 − x )1 2 dx. Show that, for a < b, ∫ q p ( x − a b − x )1 2 dx = (b − a)(π + 3√ 3 − 6) 12 , where p = ???????????????????????????

User Gooshan
by
4.9k points

1 Answer

4 votes

If the integral as written in my comment is accurate, then we have


I=\displaystyle\int_(3/2)^2√((x-1)(3-x))\,\mathrm dx

Expand the polynomial, then complete the square within the square root:


(x-1)(3-x)=-x^2+4x-3=1-(x-2)^2


I=\displaystyle\int_(3/2)^2√(1-(x-2)^2)\,\mathrm dx

Let
x=2-\cos\theta and
\mathrm dx=\sin\theta\,\mathrm d\theta:


I=\displaystyle\int_(\pi/3)^(\pi/2)√(1-(2-\cos\theta-2)^2)\sin\theta\,\mathrm d\theta


I=\displaystyle\int_(\pi/3)^(\pi/2)√(1-\cos^2\theta)\sin\theta\,\mathrm d\theta


I=\displaystyle\int_(\pi/3)^(\pi/2)√(\sin^2\theta)\sin\theta\,\mathrm d\theta

Recall that
√(x^2)=|x| for all
x, but for all
\theta in the integration interval we have
\sin\theta>0. So
√(\sin^2\theta)=\sin\theta:


I=\displaystyle\int_(\pi/3)^(\pi/2)\sin^2\theta\,\mathrm d\theta

Recall the double angle identity,


\sin^2\theta=\frac{1-\cos(2\theta)}2


I=\displaystyle\frac12\int_(\pi/3)^(\pi/2)(1-\cos(2\theta))\,\mathrm d\theta


I=\frac\theta2-\frac{\sin(2\theta)}4\bigg|_(\pi/3)^(\pi/2)


I=\frac\pi4-\left(\frac\pi6-\frac{\sqrt3}8\right)=\boxed{\frac\pi{12}+\frac{\sqrt3}8}

You can determine the more general result in the same way.


I=\displaystyle\int_p^q√((x-a)(b-x))\,\mathrm dx

Complete the square to get


(x-a)(b-x)=-(x-a)(x-b)=-x^2+(a+b)x-ab=\frac{(a+b)^2}4-ab-\left(x-\frac{a+b}2\right)^2

and let
c=\frac{(a+b)^2}4-ab for brevity. Note that


c=\frac{(a+b)^2}4-ab=\frac{a^2-2ab+b^2}4=\frac{(a-b)^2}4


I=\displaystyle\int_p^q\sqrt{c-\left(x-\frac{a+b}2\right)^2}\,\mathrm dx

Make the following substitution,


x=\frac{a+b}2-\sqrt c\,\cos\theta


\mathrm dx=\sqrt c\,\sin\theta\,\mathrm d\theta

and the integral reduces like before to


I=\displaystyle\int_P^Q√(c-c\cos^2\theta)\,\sin\theta\,\mathrm d\theta

where


p=\frac{a+b}2-\sqrt c\,\cos P\implies P=\cos^(-1)\frac{\frac{a+b}2-p}{\sqrt c}


q=\frac{a+b}2-\sqrt c\,\cos Q\implies Q=\cos^(-1)\frac{\frac{a+b}2-q}{\sqrt c}


I=\displaystyle\frac{\sqrt c}2\int_P^Q(1-\cos(2\theta))\,\mathrm d\theta

(Depending on the interval [p, q] and thus [P, Q], the square root of cosine squared may not always reduce to sine.)

Resolving the integral and replacing c, with


c=\frac{(a-b)^2}4\implies\sqrt c=\frac2=\frac{b-a}2

because
a<b, gives


I=\frac{b-a}2(\cos(2P)-\cos(2Q)-(P-Q))

Without knowing p and q explicitly, there's not much more to say.

User FloatingLomas
by
5.4k points